Extending the Ansell Gash Model with Collaborative Capacity, Institutional Learning, and Collaborative Sustainability in Disaster - Sholahuddin Shoum Abdurrohman; Evi Satispi; Muhamad Yusuf (SWATANTRA, 2026)
Collaborative governance has become a dominant lens for understanding how disasters, as wicked problems, are managed through cross-sectoral partnerships. The model developed by Ansell and Gash (2008) comprising starting conditions, institutional design, facilitative leadership, and collaborative process remains the most widely used framework, yet it stops at the point where collaborative action is produced, without explaining what happens after collaboration has been successfully established. Drawing on a sequential explanatory mixed-methods study of the collaboration between the Regional Disaster Management Agency (BPBD) and Muhammadiyah Disaster Management Center (MDMC) in flood mitigation in Palangka Raya City, Indonesia, this conceptual article argues that collaboration in the disaster context is evolutionary rather than something that ends at a single endpoint. The article proposes extending the Ansell Gash model with three additional constructs Collaborative Capacity, Institutional Learning, and Collaborative Sustainability interconnected through the cross-cutting element of Shared Mission. These three constructs are theoretically positioned against the literature on collaborative governance regimes, network governance, collaborative inertia, organizational learning theory, social capital, and the literature on faith-based organizations, and their implications for disaster governance theory and practice are discussed. This article contributes a more complete, empirically grounded model for understanding how collaboration in disaster management moves from formation toward institutionalization.